2014
DOI: 10.1111/ejh.12300
|View full text |Cite
|
Sign up to set email alerts
|

Deferasirox for transfusion‐dependent patients with myelodysplastic syndromes: safety, efficacy, and beyond (GIMEMA MDS0306 Trial)

Abstract: Deferasirox therapy in transfusion-dependent patients with MDS was moderately well tolerated and effectively lowered serum ferritin levels. Positive hematological responses were observed, and a subset of patients achieved transfusion independence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
90
1
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 94 publications
(112 citation statements)
references
References 47 publications
(71 reference statements)
18
90
1
3
Order By: Relevance
“…Erythroid response rates range between 11 and 22%. Table 1 Clinical trials showing erythropoietic improvement during iron chelation therapy in patients with lower risk MDS [27][28][29][30].…”
Section: Iron Overload and Bone Marrow Functionmentioning
confidence: 99%
See 2 more Smart Citations
“…Erythroid response rates range between 11 and 22%. Table 1 Clinical trials showing erythropoietic improvement during iron chelation therapy in patients with lower risk MDS [27][28][29][30].…”
Section: Iron Overload and Bone Marrow Functionmentioning
confidence: 99%
“…Using strict criteria for erythroid response, a prospective Italian multicenter study found that during 12 months of treatment with DFX, RBC transfusion requirement declined significantly from a median of 3 to a median of 1 RBC units per month [30]. The cumulative incidence of transfusion independence increased from 2.6% at 6 months to 15.5% at 12 months.…”
Section: Iron Overload and Bone Marrow Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although mainly obtained from retrospective trials, data indicate that DFX might improve survival and reduce morbidity in such patients. Moreover, improvement of hematopoiesis during DFX treatment was reported by several groups with erythroid, neutrophil and platelet responses seen in 6-21%, 3-17%, and 15-30% of the patients, respectively, including transfusion independency for PRBC at 12 months of DFX treatment of 12% in a trial from the Italian GIMEMA group [33][34][35].…”
Section: Potential Benefits Of Iron Chelation In Transfusion Dependenmentioning
confidence: 87%
“…DFX has shown its efficacy in sufficiently reducing serum ferritin in transfusion dependent patients with MDS and IOL [30][31][32][33][34]. Although mainly obtained from retrospective trials, data indicate that DFX might improve survival and reduce morbidity in such patients.…”
Section: Potential Benefits Of Iron Chelation In Transfusion Dependenmentioning
confidence: 99%